High : everything you want to know about drugs, alcohol, and addiction - Sheff, David; Sheff, Nic (Houghton Mifflin Harcourt, 2020)
David and Nic Sheff, the father and son authors, relate Nic's struggle with addiction and how he became sober. Features factual information on various drugs, alcohol, and addiction, discusses the risks of experimenting, and includes the latest research, interviews, and real-life testimonials that show what drug and alcohol use really looks like. Also discusses the steps of treatment, relapse, and recovery. Includes an addiction self-test for teens, a conversation between the authors, a glossary of terms, emergency numbers and other resources, and a list of helpful books.